The unique characteristics of intussusception after renal tumor surgery in children - S.E. van Peer; C.P. van de Ven; C.E.J. Terwisscha van Scheltinga; J.A. Hol; M.H.W.A. Wijnen; A.S. Littooij; M. van Grotel; M.M. van den Heuvel-Eibrink (Elsevier, 2018)
Introduction: To further optimize survival rates as well as quality of cure for pediatric kidney tumors, attention for treatment related morbidity and mortality has become increasingly important. Intussusception is a rare but important complication after tumornephrectomy in children, causing morbidity, mortality and prolonged hospitalization. In this study, we describe two recent cases in our institute and provide a comprehensive review of the literature. Methods: For our narrative review, we searched for all reported cases of post tumor nephrectomy intussusception published until November 2016, using Pubmed and Embase libraries. Results: A total of 52 pediatric renal tumor cases who developed intussusception after tumor nephrectomy were identified. Median age was 23 months (range 3-84). Median time of onset was postoperative day 6 (range 1-18). Of 41 patients described in detail, only 4/41 were ileocolic, the others suffered from a small bowel intussusception. Most frequent presenting symptom was bilious vomiting. Preceding treatment approach was documented in 47 cases; i.e. preoperative chemotherapy had been administered to 10/47 patients. In 29 of 30 well documented cases, successful manually reduction during re-laparotomy was described and only 1 patient needed resection. All patients survived without recurrence of intussusception. Conclusion: In pediatric renal tumor patients, small bowel obstruction seems to reflect mostly post nephrectomy intussusception cases in contrast to the ileocolic idiopathic intussusceptions that are observed in healthy children. Symptoms of intussusception mimic chemotherapy related toxicity and general post-surgical symptoms, thereby initiating a significant delay in diagnosis. Awareness of intussusception after renal tumor surgery is warranted.